Les travaux et les jours - Winter, C.W (Capricci, 2022)
"The Works and Days (of Tayoko Shiojiri in the Shiotani Basin), the second feature from directors C.W. Winter and Anders Edström, is an eight-hour fiction shot for a total of 27 weeks, over a period of 14 months, in a village of 47 inhabitants in the mountains of Kyoto Prefecture, Japan. It is a geographic description of the work and non-work of a farmer. A portrait, over five seasons, of a family, of a terrain, of a soundscape, and of duration itself. It is a film that takes the time to spend time and hear people out. A film-as-adaptive-landscape. A georgic in five books featuring a performance by Tayoko Shiojiri that binds fiction and actual bereavement into a heartbreaking indeterminability. [...]" [berlinale.de/en/archive]
Original: USA, Schweden, Japan, Großbritannien 2020
Bildformat 1.5:1
Keywords: Film; DVD-Video